Role of Budgeting Practices in Service Delivery in Ghana's Public Sector - Scott, George Kojo; Enu-Kwesi, Francis (Modern Perspectives in Economics, Business and Management Vol. 4, 2021)
This research analysed the role of budgeting as practised in the Ghanaian public sector towards service delivery. The research adopted a mixed-method research design where qualitative and quantitative data were gathered using questionnaires, interviews, focus group discussions, and document analysis. The study used multistage sampling to pick the respondents for the questionnaires, key interview informants, and the participants in the focus group discussions. Thirty four out of 170 district assemblies that existed by 2008 were sampled. Participants in the study included 612 District Assembly (DA) officials, 1020 citizens, 28 national/regional officials, and 20 participants in focus group discussions. Quantitative data, measured using Likert scale questionnaire items, were analysed using descriptive statistics and regression, while qualitative data were examined thematically. The findings showed that citizens rated service delivery poorly, while district assembly officials rated service delivery as satisfactory. The study established that budgeting practices had a positive and significant influence on service delivery. The study findings have significant implications on the public administrators, citizens and scholars as it established the importance of proper budgeting practices if the public sector decentralised governments and agencies will be able to deliver satisfactory services to the public, especially in the African context.